The preparation of liquefied bio-stalk carbon nanofibers and their application in supercapacitors - Jiang, Xia; Liu, Chao; Shi, Gaofeng; Wang, Guoying; Wang, Zhao; Jia, Shiming; Dong, Yucan; Mishra, Puranjan; Tian, Haoqi; Liu, Yanrong (Royal Society of Chemistry, 2019)
Carbon nanofibers (CNFs) have been widely used in electrochemical energy storage devices because of their excellent conductivity, extremely large surface area and structural stability. Herein, we obtained a viscous, liquefied bio-stalk carbon via the simple chemical treatment of biomass, and mixed it with polyacrylonitrile to prepare a spinning solution. Subsequent electrospinning and high temperature activation resulted in the successful preparation of liquefied lignin-based activated carbon nanofibers. The as-prepared liquefied bio-stalk carbon nanofibers exhibited an outstanding electrochemical performance (specific capacitance of 273 F g−1 at 0.5 A g−1 current density), and a capacitance retention of 210 F g−1 even under a large current density of 10 A g−1. Besides its high specific capacitance and outstanding rate capability, the symmetrical supercapacitor cell based on the liquefied carbon-based nanofiber electrodes also exhibited an excellent cycling performance with 92.76% capacitance retention after 5000 charge–discharge cycles. This study provides a new strategy for the future development of supercapacitor electrode materials and enhances the development of biomass energy.